Dynamic Load balancing Approaches with Optimal Virtual Machine Migration in Cloud Environments - Suresh Jain, Kailash Chandra Bandhu, Rudresh Shah (International Journal of Intelligent Systems and Applications in Engineering, 2024)
In recent years, Cloud Computing has become increasingly appealing to service providers seeking to run applications on large data centres, primarily due to the advantages of highly available hardware, on-demand provisioning, and pay-as-you-go models. This technology harnesses the power of virtualization, which allows for the consolidation of multiple Virtual Machines (VMs) onto a minimal number of servers. By employing dynamic VM provisioning, VM consolidation, and strategically switching servers on and off as needed, data centres can maintain the desired Quality-of-Service (QoS) while achieving greater server utilization and energy efficiency. In our proposed work, we focus on managing the inter-relationship between energy consumption, the number of VM migrations, SLA (Service Level Agreement) violations, and application performance. Our approach tackles the issue of over-utilized servers by migrating the most suitable VMs to appropriate destination servers. To accomplish this, we have devised VM selection and VM placement strategies. Additionally, for overload detection, we have utilized the exponential smoothing technique. Our chosen platform for implementing these approaches is the cloudsim simulator. The results of our study demonstrate significant benefits. Specifically, we observed a reduction in energy consumption of up to 17.57%, a decrease in the number of VM migrations, and overall improvements in application performance across various scenarios.